Studi Konfigurasi Susunan & Material Pengisi Pada Ban Bekas Sebagai Solusi Alternatif Dinding Penahan Tanah - Michael Limanow; Andryan Suhendra (JMTS: Jurnal Mitra Teknik Sipil, 2022)
Recycling processed used tyres and alternative solution of earth retaining materials that cost-effective, environmental friendly, prompted the study of using waste tyres as geotechnical structures’ material. Studies show that the use of waste tyres, either whole scrap tyre, shredded to chips or flakes, granulated and powdered, are feasible as reinforcement material for retaining structure. This time, an idea arose to analyze the reuse of whole scrap tyres for Retaining Wall as an alternate substitution to Gabion wall. The purpose of this analysis is to measure the behavior and the effectiveness of waste tyre as a retaining wall with variety of stack configurations and types of tyre filler. On the analysis, manual calculations were carried out with the help of Plaxis 2D program and literature studies to compare and complete the analysis of the retaining walls’ behavior. Sand embankment behind the retaining wall is 6 meters height. The analysis shows that waste tyre retaining wall is more effective and a proper alternative retaining wall compared to Gabion wall.